The Efficacy of Surfactant Replacement Therapy in the Growth-Restricted Preterm Infant: What is the Evidence? - Malhotra, Atul; Sasi, Arun; Miller, Suzanne L.; Jenkin, Graham; Polglase, Graeme R. (Frontiers in Pediatrics, 2014)
Background: Surfactant replacement therapy (SRT) is an integral part of management of preterm surfactant deficiency (respiratory distress syndrome, RDS). Its role in the management of RDS has been extensively studied. However its efficacy in the management of lung disease in preterm infants born with intrauterine growth restriction (IUGR) has not been systematically studied. Objective: To evaluate the efficacy of exogenous surfactant replacement therapy in the management of preterm IUGR lung disease. Methods: A systematic search of all available randomised clinical trials (RCT) of surfactant replacement therapy in preterm IUGR infants was done according to the standard Cochrane collaboration search strategy. Neonatal respiratory outcomes were compared between the preterm IUGR and appropriately-grown for gestational age (AGA) preterm infant populations in eligible studies. Results: No study was identified which evaluated the efficacy or responsiveness of exogenous surfactant replacement therapy in preterm IUGR infants as compared to preterm AGA infants. The only study identified through the search strategy used small for gestational age (SGA; defined as less than 10th centile for birth weight) as a proxy for IUGR. The RCT evaluated the efficacy or responsiveness of SRT in preterm SGA group as compared to AGA infants. The rate of intubation, severity of RDS, rate of surfactant administration, pulmonary air leaks and days on the ventilator did not differ between both groups. However, the requirement for prolonged nasal CPAP (p< 0.001), supplemental oxygen therapy (p <0.01) and the incidence of bronchopulmonary dysplasia at 28 days and 36 weeks (both p<0.01) was greater in SGA infants. Discussion: There is currently insufficient data available to evaluate the efficacy of SRT in preterm IUGR lung disease. A variety of research strategies will be needed to enhance our understanding of the role and rationale for use of surfactant replacement therapy in preterm IUGR l